A MODERN APPROACH TO ELIMINATE POST-BURN CONTRACTURES OF THE SHOULDER AND ELBOW JOINTS IN CHILDREN (CAHIERS MAGELLANES-NS, 2024)
This article presents a comparison between modern and traditional methods of surgical treatment of post-burn cicatricial contractures in the area of the shoulder  and elbow joint in children. Currently, the number of children suffering from burns is steadily increasing. Despite the fact that modern methods of treating burns have significantly reduced the number of deaths, they have not solved the problem with the increase in the number of disability after severe burns in children. In 20-22% of cases, complications of post-burn diseases are observed in children. In the form of trophic ulcers, cotractures of joints and tissue destruction. Therefore, the rehabilitation of such patients is of great social and economic importance.Restoring the function of organs that have been lost as a result of complications after burns is the main task of reconstructive surgery. According to some authors, 40-75% of patients after severe burns need reconstructive surgery.